Estrogen Receptor Alpha as a Key Target of Red Wine Polyphenols Action on the Endothelium - Chalopin, Matthieu (Public Library of Science, 2010)
BACKGROUND: A greater reduction in cardiovascular risk and vascular protection associated with diet rich in polyphenols are generally accepted; however, the molecular targets for polyphenols effects remain unknown. Meanwhile evidences in the literature have enlightened, not only structural similarities between estrogens and polyphenols known as phytoestrogens, but also in their vascular effects. We hypothesized that alpha isoform of estrogen receptor (ERα) could be involved in the transduction of the vascular benefits of polyphenols. METHODOLOGY/PRINCIPAL FINDINGS: Here, we used ERα deficient mice to show that endothelium-dependent vasorelaxation induced either by red wine polyphenol extract, Provinols™, or delphinidin, an anthocyanin that possesses similar pharmacological profile, is mediated by ERα. Indeed, Provinols™, delphinidin and ERα agonists, 17-beta-estradiol and PPT, are able to induce endothelial vasodilatation in aorta from ERα Wild-Type but not from Knock-Out mice, by activation of nitric oxide (NO) pathway in endothelial cells. Besides, silencing the effects of ERα completely prevented the effects of Provinols™ and delphinidin to activate NO pathway (Src, ERK 1/2, eNOS, caveolin-1) leading to NO production. Furthermore, direct interaction between delphinidin and ERα activator site is demonstrated using both binding assay and docking. Most interestingly, the ability of short term oral administration of Provinols™ to decrease response to serotonin and to enhance sensitivity of the endothelium-dependent relaxation to acetylcholine, associated with concomitant increased NO production and decreased superoxide anions, was completely blunted in ERα deficient mice. CONCLUSIONS/SIGNIFICANCE: This study provides evidence that red wine polyphenols, especially delphinidin, exert their endothelial benefits via ERα activation. It is a major breakthrough bringing new insights of the potential therapeutic of polyphenols against cardiovascular pathologies.